KRAS mutant rectal cancer cells interact with surrounding fibroblasts to deplete the extracellular matrix. Issue 10 (15th June 2021) - Kim, Jin K.; Marco, Michael R.; Choi, Seo‐Hyun; Qu, Xuan; Chen, Chin‐Tung; Elkabets, Moshe; Fairchild, Lauren; Chow, Oliver; Barriga, Francisco M.; Dow, Lukas E.; O'Rourke, Kevin; Szeglin, Bryan; et al.
Abstract : Somatic mutations in the KRAS oncogene are associated with poor outcomes in locally advanced rectal cancer but the underlying biologic mechanisms are not fully understood. We profiled mRNA in 76 locally advanced rectal adenocarcinomas from patients that were enrolled in a prospective clinical trial and investigated differences in gene expression between KRAS mutant (KRAS‐mt) and KRAS ‐wild‐type (KRAS‐wt) patients. We found that KRAS‐mt tumors display lower expression of genes related to the tumor stroma and remodeling of the extracellular matrix. We validated our findings using samples from The Cancer Genome Atlas (TCGA) and also by performing immunohistochemistry (IHC) and immunofluorescence (IF) in orthogonal cohorts. Using in vitro and in vivo models, we show that oncogenic KRAS signaling within the epithelial cancer cells modulates the activity of the surrounding fibroblasts in the tumor microenvironment. Abstract : Oncogenic KRAS is associated with poor outcomes in locally advanced rectal cancer (LARC) but the underlying biologic mechanisms are not fully understood. We investigated differences in gene expression profiles between KRAS mutant and KRAS wild‐type LARC tumors. We found that KRAS mutant tumors display lower expression of genes related to the tumor stroma and remodeling of the extracellular matrix.